FAKTOR-FAKTOR YANG MEMPENGARUHI PRAKTIK TRANSFER PRICING: BUKTI DARI PERUSAHAAN SEKTOR ENERGI INDONESIA - B. Sundari; Rio Rivan Prayoga (Universitas Pattimura, 2025)
This study aims to analyze the factors that influence transfer pricing practices in Indonesian public energy companies during the period 2021–2024. The variables tested include taxes, leverage, foreign ownership, and foreign exchange rates, both partially and simultaneously. The research sample consists of 16 energy companies listed on the Indonesia Stock Exchange, resulting in 64 company-year observations. Data were obtained from annual reports and financial statements, then analyzed using panel data regression with EViews 12. The results show that taxes and exchange rates have a significant effect on transfer pricing practices, while leverage and foreign ownership have no significant effect. However, simultaneously, all independent variables were found to influence transfer pricing practices. These findings confirm the important role of tax policy and macroeconomic stability in controlling transfer pricing practices in the energy sector.